Peran Nilai Hindu “Tri Kaya Parisudha” dalam Peningkatan Loyalitas Wisatawan Terhadap Desa Wisata Pedawa, Bali Utara - Nyoman Dini Andiani; I Made Antara; Wayan Ardika; Nyoman Sunarta (Pusat Kajian Bali Universitas Udayana, 2020)
Local wisdom based on Hinduism Tri Kaya Parisudha has an important role in the development of tourism in Pedawa Village, North Bali. This article analyzes the role of Tri Kaya Parisudha's values and practices as a spirit of hospitality in increasing the loyalty of tourists to visit Pedawa Village, one of the five ancient villages in Banjar District, Buleleng Regency. This qualitative study begins with data collection with field observations and interviews with thirty foreign and domestic tourists who have visited Pedawa Village more than once. The results showed that the loyalty of returning tourists was due to the friendliness, way of life, way of speaking and acting in the community which made tourists feel comfortable. In addition, it is also due to the uniqueness of the traditional house of Pedawa Village as a tourist attraction. The life habits of the Pedawa people that reflect the values of the Tri Kaya Parisudha have implications not only for the sustainability of tourism villages but also for strengthening the appreciation and practices of Hindu-based local wisdom in Pedawa Village.